Digital Forensic Accounting in the Era of Cybercrime: A Global Bibliometric Review - Nurul Maghfirah Surianto; Ricky Setiawan (Pattimura Proceeding, 2026)
This study uses bibliometric analysis to examine developments and research trends in the field of forensic accounting from 2005 to 2025. Publication data extracted from the Scopus database is analyzed using VOSviewer software to map statistical patterns, visualize academic networks, and identify key research topics in this field. The results reveal dynamic shifts in publication volume caused by factors such as the increasing complexity of financial crime, advances in the integration of digital technologies, heightened expectations for transparency, evolving regulatory frameworks, increased interdisciplinary collaboration, and improved internal control mechanisms. The high volume of journal articles indicates strong global academic interest. In addition, the analysis highlighted significant contributions from both developed and emerging economies, including the United States, India, United Kingdom, Indonesia, South Korea and Australia. Key research topics include risk management, fraud detection, digital forensics, fraud analysis, digital compliance, and financial governance. This study underscores the ongoing need for research to improve fraud detection and prevention strategies, promote global academic collaboration, and strengthen efforts to maintain financial integrity and transparency